Echolalia Communication for Autism: An Introduction - Muhammad Dalimunte; Sholihatul Hamidah Daulay; Rabi’atun Adawiyah (AL-ISHLAH: Jurnal Pendidikan, 2022)
Autism comes from the Greek phrase vehicles this means that self. Autism isn't always a kind of disorder however is a complicated developmental sickness resulting from harm to the brain, usually may be detected on account that the kid is born or at the age of a toddler. One of the problems confronted by autistic kids in communication, particularly for kids who enjoy intense barriers, is in gaining knowledge of language and speech. The issue of autistic kids in speaking is because of experiencing language disorders (verbal and non-verbal), despite the fact that language is the principal medium of communication. The purpose of this study was to investigate the phenomenon of echo-influenced communication in children with autism. In this study, researchers use a qualitative approach to explain existing reality. The main informants for this study were teachers at the Emotionally Focused Therapy Center and teachers at the Behavior Therapy Center. The results of the study are that learning to communicate with nonverbal children with autism is by communicating the concept of language through visual media, with teachers asking questions and children answering things with their abilities. Communication difficulties in children with autism are due to language disorders (linguistic and nonverbal), but language is the most important medium of communication. They often find it difficult to convey their desires both verbally (verbally / speaking) and non-verbally (gesturing / gesturing and writing). Most of them can speak and use short sentences with basic vocabulary, but their vocabulary is limited and their language is difficult to understand.